Dealing with Donald Trump - Gabriel Felbermayr (Intereconomics, 2018)
The logic for multilateral cooperation in trade and beyond becomes stronger, not weaker. A new governance forum will emerge, where negotiating will take place in country clubs instead of among members at the WTO. However, by breaking protocol, the US president has gained substantial bargaining power, because he puts himself in a situation in which he actually has to implement his threats if the negotiation counterparts do not confirm in order to save face on the domestic and global stages.
Keywords: 330; European governance; Protectionism; Trade disputes; Trade policy; Trade restrictions; USA; WTO